Leverage Ratios for Different Bank Business Models - David Grossmann (Credit and Capital Markets – Kredit und Kapital, 2017)
The development of the Basel III leverage ratio does not consider the different risk characteristics of bank business models. All banks have to achieve the same requirements even if a high-risk business model is chosen. For that reason, leverage ratios which are adjusted to the risk-profile of retail, wholesale, and trading banks are developed. Based on Value-at-Risk and Expected Shortfall calculations, the left-hand tail of a net return on non-risk-weighted assets distribution of 120 European banks is analyzed. Retail banks are less risky and can withstand financial distress with a smaller amount of capital. – – Verschuldungsquoten für unterschiedliche Bank-Geschäftsmodelle Bei der Entwicklung der Verschuldungsquote nach Basel III wurden die unterschiedlichen Risikomerkmale von Bank-Geschäftsmodellen nicht berücksichtigt. Alle Banken müssen die gleichen Anforderungen erfüllen, auch wenn ein risikoreiches Geschäftsmodell gewählt wird. Aus diesem Grund werden Verschuldungsquoten hergeleitet, die sich an dem Risikoprofil von Retail-, Wholesale- und Trading-Banken orientieren. Auf Basis von Value-at-Risk und Expected-Shortfall Berechnungen wird eine Renditeverteilungskurve, die als Jahresüberschuss nach Steuern im Verhältnis zur nicht-risikogewichteten Aktiva ermittelt wird, von 120 europäischen Banken analysiert. Retail-Banken sind weniger riskant und können finanziellen Stresssituationen mit einer geringeren Kapitaldecke standhalten.
Keywords: G21; G28; G32; 330; Bank Business Models; Bank Capital Requirements; Expected Shortfall; Leverage Ratio; Regulation; Value-At-Risk